Changes in the Distribution of the α3 Na+/K+ ATPase Subunit in Heterozygous Lurcher Purkinje Cells as a Genetic Model of Chronic Depolarization during Development - Rebecca McFarland; Hadi S. Zanjani; Jean Mariani; Michael W. Vogel (International Journal of Cell Biology)
A common assumption of excitotoxic mechanisms in the nervous system is that the ionic imbalance resulting from overstimulation of glutamate receptors and increased Na+ and Ca++ influx overwhelms cellular energy metabolic systems leading to cell death. The goal of this study was to examine how a chronic Na+ channel leak current in developing Purkinje cells in the heterozygous Lurcher mutant (+/Lc) affects the expression and distribution of the α3 subunit of the Na+/K+ ATPase pump, a key component of the homeostasis system that maintains ionic equilibrium in neurons. The expression pattern of the catalytic α3 Na+/K+ ATPase subunit was analyzed by immunohistochemistry, histochemistry, and Western Blots in wild type (WT) and +/Lc cerebella at postnatal days P10, P15, and P25 to determine if there are changes in the distribution of active Na+/K+ ATPase subunits in degenerating Purkinje cells. The results suggest that the expression of the catalytic α3 subunit is altered in chronically depolarized +/Lc Purkinje cells, although the density of active Na+/K+ ATPase pumps is not significantly altered compared with WT in the cerebellar cortex at P15, and then declines from P15 to P25 in the +/Lc cerebellum as the +/Lc Purkinje cells degenerate.